X-Linked Lymphoproliferative Disease Mimicking Multisystem Inflammatory Syndrome in Children—A Case Report - Prader, Seraina; Ritz, Nicole; Baleydier, Frédéric; Andre, Maya C.; Stähli, Noémie; Schmid, Kevin; Schmid, Hanna; Woerner, Andreas; Diesch, Tamara; Meyer Sauteur, Patrick M.; Trück, Johannes; Gebistorf, Fabienne; et al. (Frontiers in Pediatrics, 2021)
Most children with a SARS-CoV-2 infection are asymptomatic or exhibit mild symptoms. However, a small number of children develop features of substantial inflammation temporarily related to the COVID-19 also called multisystem inflammatory syndrome in children (MIS-C) or pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS), clinically similar to Kawasaki disease, toxic shock syndrome and hemophagocytic lymphohistiocytosis (HLH). It is well known that genetic predisposition plays an important role in virally-triggered diseases such as Epstein-Barr virus (EBV)-associated HLH, while this has not yet been established for patients with MIS-C. Here we describe a male patient fulfilling the diagnostic criteria of MIS-C, who was initially treated according to current consensus guidelines. Presence of hypofibrinogenemia, normal lymphocyte counts and C-reactive protein, but substantial hyperferritinemia distinguish this patient from others with MIS-C. The clinical course following initial presentation with acute respiratory distress syndrome was marked by fatal liver failure in the context of EBV-associated HLH despite treatment with steroids, intravenous immunoglobulins, interleukin (IL)-1 receptor blockade and eventually HLH-directed treatment. X-linked lymphoproliferative disease type 1 (XLP1), a subtype of primary HLH was diagnosed in this patient post mortem. This case report highlights the importance of including HLH in the differential diagnosis in MIS-C with severe disease course to allow specific, risk-adapted treatment and genetic counseling.